The Influence Of Dokuku Data Security And Service-Oriented Architecture On The Quality Of Information - Algifanri Maulana; Harisno . (Jurnal Nasional Teknologi dan Sistem Informasi, 2016)
The Goals of this research were to gain an overview of the influence Dokuku data security and service-oriented architecture to quality information. The population in this study include Dokuku application of existing users in the city of Batam. Determination of the number of samples using Taro Yamane formula, and the determination of the respondents were 97 people by using simple random sampling method is taken from the user population Dokuku application. Data analysis includes descriptive analysis and verification. The final conclusion is that data security Dokuku affect the quality of information. While partially oriented architecture does not affect the quality of information, but simultaneously turns Dokuku data security and service-oriented architecture affects the quality of the information.